Related Strategies and Practices of News Institutions in Dealing with News Text Addressing Issues of Islamists (Study Case: BBC World and Al-Arabiya 2022) - Alrashid, Hind Saad (Arab Journal for Sciences and Research Publishing, 2024)
This study aimed at identifying news institutions' translation methods and practices to show effect translation practices and policies influence news text output addressing the Islamist discourse.An ethnographic approach is used of conducts a comparative fieldwork analysis and textual analysis of news reports collected between the BBC and Al Arabia media institutions, where it explores the practices and news institutions' translation methods of translation agents in the two news platforms; the English and the Arabic. Results of the study show that the translation strategies and practices of News Institutions in dealing with the texts related to Islamist discourse mainly are deletion, omission, addition, direct quotation, and indirect speech reporting. This study describes the translation strategies and practices of News Institutions in dealing with the texts related to Islamist discourse reveals that strategies used; do not follow one language direction route in their application in the reports or one pattern. The study shows that the translation practices are relate to text selection, news input and the agents. The study concludes by suggesting that an increased awareness of these issues would assist News Institutions to make more effective used of the translation strategies and practices in their new reports related to Islamist discourse.
Keywords: strategies; News Text; News Institutions; Islamist discourse; translation practices